PENGGUNAAN LANGKAH LANGKAH MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS XI IPA 2 SEMESTER 1 SMA NEGERI 8 DENPASAR TAHUN PELAJARAN 2018/2019 - I Gusti Ngurah Agung Indrayana (LP3M Universitas PGRI Mahadewa Indonesia, 2022)
The learning model is a conceptual framework that describes a systematic procedure in organizing the learning experience to achieve a certain level of learning. Problem based learning learning model is problem based learning. The purpose of this study was to determine how high the increase in students' learning achievement in mathematics was after using the steps of the Problem Based Learning model in learning. The research flow begins with planning, action, observation and finally reflection. The research subjects were all students of class XI IPA 2 SMA Negeri 8 Denpsar in semester 1 of the 2018/2019 academic year. The object of this research is the improvement of student achievement. The method used is descriptive method. For quantitative data, it is analyzed by finding the mean, median, mode, making class intervals and presenting it in the form of tables and graphs. From the results of the study (1) From the initial data there were 23 students who scored below the KKM and in the first cycle it decreased to 11 students and in the second cycle only 5 students scored below the KKM. (2) From the initial average of 70.77, it rose to 76.83 in the first cycle and in the second cycle it rose to 81.06. (3) From the initial data, the percentage of learning completeness was 51.06%, while in the first cycle it increased to 76.59% and in the second cycle it increased again to 89.36%.